2017
DOI: 10.1016/j.omtn.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of miR-7 Operated by TTF-1 Promoter Inhibited the Growth of Human Lung Cancer through the NDUFA4 Pathway

Abstract: Targeted expression of gene technique is an important therapeutic strategy for lung cancer. MicroRNA-7 has been well documented as a promising tumor suppressor but never been test in specific gene-promoter-targeted expression in cancer gene therapy. Here, we first evaluated the efficacy of miR-7 expression operated by the promoter of TTF-1, a lineage-specific oncogene in lung cancer, in vitro using an eukaryotic vector of TTF-1-promoter-operated expression of miR-7 (termed as p-T-miR-7). Interestingly, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…The present study showed that lncMIF‐AS1 can positively regulate the expression of NDUFA4. NDUFA4 encodes a protein belonging to the respiratory chain of mitochondria, which has been implicated in the development of various cancers including renal cell carcinoma and lung cancer . Herein, our study demonstrates that the expression of NDUFA4 is positively regulated by lncMIF‐AS1 in a micro RNA (miR)‐212‐5p‐targeting competitive endogenous way.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present study showed that lncMIF‐AS1 can positively regulate the expression of NDUFA4. NDUFA4 encodes a protein belonging to the respiratory chain of mitochondria, which has been implicated in the development of various cancers including renal cell carcinoma and lung cancer . Herein, our study demonstrates that the expression of NDUFA4 is positively regulated by lncMIF‐AS1 in a micro RNA (miR)‐212‐5p‐targeting competitive endogenous way.…”
Section: Introductionmentioning
confidence: 80%
“…NDUFA4 gene is located on chromosome 7p21.3, which encodes a subunit of the electron transport chain complex belonging to the respiratory chain of mitochondria to produce ATP . Lei et al found that downregulation of NDUFA4 could contribute to the growth and metastasis of human lung cancer cells through altering the transduction of the Akt and Erk pathways. Downregulated NDUFA4 has also been detected in clear cell renal cell carcinoma, lung cancer, and esophageal squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA-7 (miR-7) was first identified by Lagos-Quintana in 2001 [9] and has been reported to regulate the biology of various tumor cells and the development of inflammation diseases by repressing the expression of different target molecules [10,11]. For instance, Fan et al found that miR-7 suppressed angiogenesis of colorectal cancer cells through ERK signaling by downregulation epidermal growth factor receptor [12].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA duplex is incorporated into the RNA-induced silencing complex, where one of the strands undergoes degradation while the other forms the mature miRNA [13]. Mature miRNAs can bind to the 3′-untranslated region of complementary or partially complementary target gene mRNA and promote the degradation of target gene mRNA at posttranscriptional level or mediate its translation inhibition, thus exerting a wide range of physiological regulatory functions [14]. In humans, more than 1,000 miRNA family members have been reported to participate in important biological processes such as cell development, differentiation, proliferation, apoptosis, tumorigenesis, and ­development.…”
Section: Introductionmentioning
confidence: 99%